Design of Plastic Wall on Lobster Trap - Gondo Puspito (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2008)
Experiment was aimed to obtain a design of lobster trap wall. The trap was constructed by plastic. Design of wall consisted of standard gap, horizontal gap, vertical gap, and rectangular gap. From those walls, it was determined the wall that was easily crawled by lobster. There were 3 groups of lobster based on body weight and carapace length, i.e. group A (10.5 cm; 10 g), group B (15.5 cm; 70 g), and group C (17 cm; 100 g). The experiment tried to find out the wall color and lobster bait first. From the experiment, lobster preferred to choose crab and red wall. While, the wall design of vertical gap was easier crawled by lobster than those of three others.  Keywords : Lobster trap wall, plastic, standard gap, horizontal gap, vertical gap, and rectangular gap.